Changes in proHB-EGF expression after functional activation of the immune system cells - T. O. Chudina; A. J. Labintsev; S. I. Romaniuk; D. V. Kolybo; S. V. Komisarenko (The Ukrainian Biochemical Journal, 2017)
The level of proHB-EGF expression on J774, Raji, KG-1 cells derived from different types of human and mouse immune system cells under the standard in vitro culture conditions and during functional activation of these cells was investigated. Changes in the proHB-EGF expression on the cell surface were found to depend on the density of cell population, the content of fetal bovine serum in the culture medium, the effect of mitogenic factors – bacterial lipopolysaccharide, an inactive full-size form of diphtheria toxin (CRM197) and recombinant soluble HB-EGF – rsHB-EGF. The results obtained are important for the understanding of the functional role of proHB-EGF receptor on the surface of macrophage-like cells and B lymphocytes and indicate the involvement of this receptor in immune response regulation in an organism.